Sistem Pakar Diagnosa Kerusakan Kendaraan Sepeda Motor Manual Menggunakan Metode Forward Chaining - Fransiskus Xaverius Pere; Putri Taqwa Prasetyaningrum (Journal of Computer and Information Systems Ampera, 2023)
Currently, motorcycles are one of the main means of transportation used to facilitate our daily activities. The use of a motorcycle can causes significant damage to the motorcycle. Because of these problems, it is necessary to analyze, design and implement an expert system that can diagnose damage to motorbikes, the process of analysis and data collection is carried out by interviewing experts in the field so that the results can be accurate. The expert system developed using the forward chaining method is an advanced search that starts from several facts to get the result, from these results an expert system can be created that can diagnose motorcycle damage accurately and can be useful for its users.